THE DEVELOPMENT OF MOBILE LEARNING MEDIA BASED ON ADOBE FLASH CS6 IN STATIC FLUID MATERIAL - Parhusip, Sartini; Siregar, Alkhafi Maas (UNIVERSITAS NEGERI MEDAN, 2022)
This research was motivated by the lack of interesting learning media innovations available for physics lessons, therefore a questionnaire was distributed and it was found that static fluid material is one of materials that is difficult for students to understand. This research aims to find out how to develop, analyze the feasibility and level of effectiveness of the mobile learning media based on adobe flash cs6 in static fluid material. The research was conducted using Research and Development with ADDIE (Analysis, Design, Development, Implementation and Evaluation) models. Respondents in this research were class XI IPA 6 students at SMAN 2 Medan. The product testing consists of small group test and large group test. Small group trials involved 10 students, and large group trials 30 students. The instrument used in this research were expert validation questionnaires, teacher validation questionnaires and determine the effectiveness of learning media by giving posttest question to students. At the validation stage of the result of the media expert assessment, the avergate percentage is 93,84% with a very decent category and result of material expert assessment get an average percentage 98% with a decent category. The result of the assessment of the physics teacher response 91,53%. The result of the learning media effectiveness test given to small and large groups get an average percentage of 70% and 86,66%. This shows that the media developed is very feasible and effective as learning media in learning activities.